2019
DOI: 10.3390/su11030842
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Law in Transformative Environmental Policies—A Case Study of “Timber in Buildings Construction in Germany”

Abstract: Over the last decades, environmental law has significantly contributed to limiting the environmental impacts of our mode of living. Yet environmental problems still prevail and are strongly linked to our production and consumption systems. Therefore, the current challenges must be tackled with a systemic approach. The concept of transformative environmental policy identifies approaches for policymakers to interfere in socio-economic systems in order to give them a more sustainable structure. This article seeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…One of the few studies on the subject is an article by Grit Ludwig. 17 She discusses the role of law in transitioning to timber construction in Germany. Based on the literature on transformative environmental policy, she divides transition 18 into three phases and notes that the role of law varies depending on the phase of the transition.…”
Section: Transformative and Adaptive Capacities Of Lawmentioning
confidence: 99%
“…One of the few studies on the subject is an article by Grit Ludwig. 17 She discusses the role of law in transitioning to timber construction in Germany. Based on the literature on transformative environmental policy, she divides transition 18 into three phases and notes that the role of law varies depending on the phase of the transition.…”
Section: Transformative and Adaptive Capacities Of Lawmentioning
confidence: 99%
“…Transformations depend on structural changes on institutional, societal, legal, and technological level. Transition-based governance strategies include necessarily several layers in their analytical preparation (Ludwig 2019).…”
Section: The Urban Bioeconomy Metabolism As a Toolbox For The Management Of Biomass Resourcesmentioning
confidence: 99%
“…Nevertheless, Milestone et al [19] indicated that there is still work to do in engaging communities and other actors in the wood value chain to increase the use of timber, especially when it is produced and used locally. Moreover, these programmes should aim to advance the use of forest resources in a sustainable way, giving priority to use in construction over the use of primary forest products as energy sources [20]. Wang et al [21] revealed that, in the UK, the trend in wood construction increasingly includes the use of hybrid structures, such as a combination of wood and steel or composites (e.g., wood and plastic).…”
Section: Introductionmentioning
confidence: 99%